Preparation method and application of biochar loaded nano zero-valent iron based on dual amino modification
By performing dual amino modification on biochar and using it for loading nano zero-valent iron, the high activity and agglomeration problems of nano zero-valent iron when removing vanadium pollutants are solved, and vanadium in water and soil are achieved. Efficient repair.
Patent Information
- Application Number
- CN202411663137.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
AI Technical Summary
The prior art has high cost, unsustainability and high activity and aggregation of nano zero-valent iron when removing vanadium pollutants in the environment, resulting in inefficient removal.
Using the preparation method of biochar-loaded nano zero-valent iron based on dual amino modification, PEI-modified nano zero-valent iron modified by PEI-protected biochar-loaded PEI-modified nano zero-valent iron is synthesized by microwave-assisted and liquid-phase reduction method for adsorption and reduction of water and soil. vanadium.
It has achieved efficient repair of vanadium in water and soil, has broad pH adaptability and stability, and can fix V (V) in soil within 30 days, significantly improving the efficiency of removing vanadium pollutants.
Smart Images

Figure CN119500066A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nano zero-valent iron preparation, and in particular to a preparation method and application of biochar-loaded nano zero-valent iron based on double amino modification. Background Art
[0002] Vanadium (V) is a silvery-white transition metal widely used in the steel and aerospace industries. In recent years, with the development of V-containing industrial activities such as fossil fuel combustion and electronic printing and dyeing, the content of anthropogenic V in the environment has increased significantly. In particular, in the process of mineral resource mining, a large amount of vanadium is released, causing serious pollution to the environment. Pentavalent vanadium (V(V)) is the main inorganic form with high toxicity, high solubility and high fluidity. At the same time, excessive V(V) enters the human body through the food chain, which can cause changes in organ morphology and function. Therefore, minimizing V pollution in water and soil is crucial to human health and environmental safety.
[0003] Currently, a variety of physical and chemical methods are used to remove V(V), including ion exchange, adsorption, chemical precipitation, flotation, coagulation-flocculation, membrane filtration and electrochemical methods, but these methods have problems such as high cost and unsustainability. Nano-zero-valent iron (nZVI) is considered to be a promising pollutant remediation material due to its high reduction ability, low pollution and cost-effectiveness. However, in practical applications, due to the high activity of nZVI, it is easily oxidized in the air. At the same time, due to its high specific surface energy and magnetic properties, nZVI is prone to agglomeration. These problems greatly reduce its efficiency in removing pollutants and also limit the effectiveness of nZVI in the environment.
[0004] In order to improve the reducing ability of nZVI, a variety of suitable materials have been designed to modify nZVI, including surface-modified nZVI, sulfided nZVI, and loaded nZVI (using carbon-based materials, clay minerals, polymers, metal-organic frameworks, COFs, etc.). Biochar (BC) is a solid material obtained by thermochemical conversion of biomass under anoxic conditions. It is considered to be an excellent carrier material for dispersing and fixing loaded nZVI due to its porous nanostructure, certain oxygen-containing functional groups, low cost, and high carbon stability. However, due to experimental and self-limiting factors, BC may exhibit some unfavorable properties, such as uneven distribution of pore structure and fewer surface polar functional groups. Therefore, in order to obtain the superior performance of BC, it needs to be modified. Summary of the invention
[0005] The purpose of the present invention is to solve the above technical problems and to provide a preparation method and application of biochar loaded with nano zero-valent iron based on double amino modification.
[0006] A preparation method of biochar-loaded nano-zero-valent iron based on dual amino modification is carried out according to the following steps:
[0007] Step S1: preparing PEI-modified biochar;
[0008] Under anaerobic conditions, biochar, polyethyleneimine, methanol and pentanediol are mixed with oxygen-free water, placed in a microwave reactor, stirred and reacted for 40 to 80 minutes at a power of 150 to 200 W and a temperature of 60 to 100° C., and then ground and passed through a 100-mesh sieve to obtain PEI-modified biochar; the mass ratio of the biochar to the polyethyleneimine is (5 to 10): (4 to 8);
[0009] Step S2: preparing PEI-modified biochar loaded with PEI-modified nZVI;
[0010] Under an inert gas environment, FeCl 2 ·4H 2 O was mixed with oxygen-free water, and then the PEI-modified biochar obtained in step S1, NaBH 4 The solution and the polyethyleneimine solution are mechanically stirred and then magnetically separated; the mixture after magnetic separation is washed and then placed in a freeze dryer for drying, and then ground and sieved to obtain biochar loaded with nano zero-valent iron based on double amino modification; the mass ratio of the PEI-modified biochar to the polyethyleneimine in the polyethyleneimine solution is (0.49-0.50): (0.12-0.13).
[0011] An application of biochar loaded with nanometer zero-valent iron based on double amino modification, wherein the biochar loaded with nanometer zero-valent iron based on double amino modification is used to remove vanadium from water and soil.
[0012] Principle of the present invention:
[0013] Polyethyleneimine (PEI) is a water-soluble linear cationic polymer that contains a large number of amino groups and has a large number of amino space branched chains, which provide abundant amino active sites for adsorption targets. Past studies have shown that BC modified with PEI can provide sufficient amine groups and adsorption sites for heavy metal adsorption, and its adsorption capacity is much higher than that of the original biochar. Therefore, it can be concluded that PEI is an excellent candidate material for heavy metal sequestration by biochar modification.
[0014] In addition, surface modification of nZVI by PEI to form PEI-nZVI nanocomposites can address the limitations of nZVI in practical applications. Many studies have shown that PEI has a wide range of functional groups, good water solubility, stable chemical properties, and strong binding ability with metals. PEI's polyelectrolyte properties, high molecular size, and excellent selective adsorption capacity for toxic anionic pollutants such as heavy metals make it more suitable for separating metal ions from dilute solutions. In addition, since PEI has a high cationic charge density, the high-density amino groups on it can combine with hydrogen ions in aqueous solution to form protonated amino groups. The negative charge of the protonated amino group is adsorbed through various interactions, including electrostatic adsorption. The lone pair of electrons on the amino group can also coordinate with metal ions for adsorption. Therefore, PEI is an ideal polymer raw material for modified adsorbents. Therefore, PEI-modified biochar-loaded nZVI is suitable for the removal of heavy metals.
[0015] Beneficial effects of the present invention:
[0016] (1) The present invention uses microwave-assisted and liquid-phase reduction methods to synthesize PEI-modified biochar loaded with PEI-modified nano zero-valent iron, and uses it to repair heavy metal vanadium in water and soil. Its repair mechanism mainly includes adsorption and reduction. Microwave-assisted synthesis technology uses the high-frequency oscillation and local heating principles of microwaves to significantly increase the reaction rate; at the same time, the energy of microwave radiation is relatively high, and the energy conversion efficiency in the medium is also relatively high. When microwaves are radiated to the reaction medium, it will cause violent vibration and friction of molecules in the medium, providing energy for the reactants, thereby intensifying the reaction. The porous structure and amino groups of biochar effectively adsorb heavy metal vanadium through pore filling and electrostatic attraction, and V(V) is absorbed by Fe 0 or Fe 2+ Reduction to V(IV) leads to Fe 0 Oxidized to Fe 2+ , then Fe 2+ Continue to participate in the reduction reaction and eventually be oxidized to Fe 3+ The protonated amino group and the intramolecular heterocyclic N also participated in the reduction of V(V), and then the N / O-containing groups fixed V(IV) on the material through the formation of complexes and precipitation.
[0017] (2) The present invention provides a heavy metal remediation agent that can be applied to both water bodies and soil, and has a wide adaptability to pH. Compared with other remediation agents, it can reduce and fix V(V) in the soil within 30 days, thereby achieving efficient remediation of heavy metal V(V) in water bodies and soil, and promoting the development and application of heavy metal remediation agents in water bodies and soil.
[0018] The present invention can obtain a preparation method and application of biochar-loaded nano zero-valent iron based on double amino modification. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 represents a scanning electron micrograph of PEI-BC@PEI-nZVI prepared in Example 1;
[0020] Figure 2 The infrared spectrum analysis diagram of PEI-BC@PEI-nZVI prepared in Example 1 is shown;
[0021] Figure 3 represents the X-ray diffraction analysis diagram of PEI-BC@PEI-nZVI prepared in Example 1, ● represents Fe 0 , ▼ represents Fe 3 O 4 ;
[0022] Figure 4 The graph represents the adsorption effect of PEI-BC@PEI-nZVI on V(V) under different pH conditions;
[0023] Figure 5 It represents the trend of the adsorption of V(V) of PEI-BC@PEI-nZVI with time;
[0024] Figure 6 The adsorption effect of PEI-BC@PEI-nZVI on V(V) under different temperature conditions is shown in Figure 2. ■ indicates 15°C, ● indicates 25°C, and ▲ indicates 35°C.
[0025] Figure 7 represents the content of V (V) in the soil after restoration by different materials in Example 1;
[0026] Figure 8 The graph shows the occurrence forms of V (V) in the soil after restoration with different materials in Example 1. DETAILED DESCRIPTION
[0027] Specific implementation method 1: This implementation method is a preparation method of biochar-loaded nano zero-valent iron based on dual amino modification, which is carried out according to the following steps:
[0028] Step S1: preparing PEI-modified biochar;
[0029] Under anaerobic conditions, biochar, polyethyleneimine, methanol and pentanediol are mixed with oxygen-free water, placed in a microwave reactor, stirred and reacted for 40 to 80 minutes at a power of 150 to 200 W and a temperature of 60 to 100° C., and then ground and passed through a 100-mesh sieve to obtain PEI-modified biochar; the mass ratio of the biochar to the polyethyleneimine is (5 to 10): (4 to 8);
[0030] Step S2: preparing PEI-modified biochar loaded with PEI-modified nZVI;
[0031] Under an inert gas environment, FeCl 2 ·4H 2 O was mixed with oxygen-free water, and then the PEI-modified biochar obtained in step S1, NaBH 4 The solution and the polyethyleneimine solution are mechanically stirred and then magnetically separated; the mixture after magnetic separation is washed and then placed in a freeze dryer for drying, and then ground and sieved to obtain biochar loaded with nano zero-valent iron based on double amino modification; the mass ratio of the PEI-modified biochar to the polyethyleneimine in the polyethyleneimine solution is (0.49-0.50): (0.12-0.13).
[0032] Specific implementation method 2: The difference between this implementation method and specific implementation method 1 is that the ratio of the mass of biochar, the volume of methanol and the mass of pentanediol to the volume of oxygen-free water described in step S1 is (0.3~0.6)g:(60~120)mL:(0.4~0.8)g:(60~120)mL.
[0033] The other steps are the same as those in the first specific implementation.
[0034] Specific embodiment three: The difference between this embodiment and specific embodiment one or two is that the biochar described in step S1 is prepared according to the following steps: Under nitrogen conditions, the soybean straw powder is heated to 300-500°C at a heating rate of 5-10°C / min, and pyrolyzed at 300-500°C for 1-2h. After the pyrolysis, it is crushed through a 100-mesh sieve to obtain biochar.
[0035] The other steps are the same as those in the first or second embodiment.
[0036] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: in step S2, FeCl 2 ·4H 2 Before mixing O with oxygen-free water, nitrogen is first passed into the oxygen-free water for 10 to 15 minutes; the FeCl 2 ·4H 2 The ratio of the mass of O to the volume of oxygen-free water is (1.779~2.668)g:(120~180)mL.
[0037] The other steps are the same as those in Specific Embodiments 1 to 3.
[0038] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: the FeCl 2 ·4H 2 O, PEI-modified biochar and NaBH 4 NaBH in solution4 The mass ratio is (1.779~2.668):(0.49~0.50):(2.22~2.23).
[0039] The other steps are the same as those in Specific Embodiments 1 to 4.
[0040] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: the NaBH 4 NaBH in solution 4 The ratio of the mass of polyethyleneimine to the volume of distilled water is (2.22-2.23) g: (40-60) mL; the ratio of the mass of polyethyleneimine in the polyethyleneimine solution to the volume of distilled water is (0.096-0.144) g: (40-60) mL.
[0041] The other steps are the same as those in Specific Embodiments 1 to 5.
[0042] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: in step S2, the PEI-modified biochar, NaBH 4 The addition interval of solution and polyethyleneimine solution was 10-15 min; NaBH 4 The injection speed of the solution and the polyethyleneimine solution was 8-10 mL / min.
[0043] The other steps are the same as those in Specific Embodiments 1 to 6.
[0044] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: the rotation speed of the mechanical stirring in step S2 is 200 to 300 rpm, and the stirring time is 30 to 40 min.
[0045] The other steps are the same as those in Specific Embodiments 1 to 7.
[0046] Specific embodiment 9: The difference between this embodiment and specific embodiments 1 to 8 is that in step S2, the mixture after magnetic separation is washed with oxygen-free ethanol and oxygen-free water in sequence, and then placed in a freeze dryer for drying for 12 to 14 hours.
[0047] The other steps are the same as those in Specific Embodiments 1 to 8.
[0048] Specific embodiment ten: This embodiment provides an application of nano-zero-valent iron loaded with biochar based on dual amino modification, and the nano-zero-valent iron loaded with biochar based on dual amino modification is used to remove vanadium from water and soil.
[0049] The following examples are used to verify the beneficial effects of the present invention:
[0050] Example 1: A method for preparing nano-zero-valent iron loaded with biochar based on dual amino modification, which is carried out according to the following steps:
[0051] Step S1: preparing PEI-modified biochar;
[0052] In nitrogen (N 2 ) conditions, the soybean straw powder was heated to 500°C at a heating rate of 10°C / min, and pyrolyzed at 500°C for 2h. After the pyrolysis, it was crushed and passed through a 100-mesh sieve to obtain biochar (BC) for later use;
[0053] Under anaerobic conditions, 0.5 g of biochar, 0.4 g of polyethyleneimine (PEI), and 90 mL of methanol (CH 3 OH) and 0.4 g pentanediol (C 5 H 12 O 2 ) was added into a beaker containing 60 mL of oxygen-free water, mixed evenly and poured into a three-necked flask (250 mL), and then placed in a microwave reactor, stirred and reacted for 60 min at a power of 184 W and a temperature of 80 ° C, and then ground and passed through a 100-mesh sieve to obtain PEI-modified biochar, which was named PBC;
[0054] Step S2: preparing PEI-modified biochar loaded with PEI-modified nZVI;
[0055] First, nitrogen was passed into the oxygen-free water for 15 min, and then 2.224 g FeCl 2 ·4H 2 O was placed in a three-necked flask containing 150 mL of oxygen-free water and stirred, and then 0.4915 g of PEI-modified biochar obtained in step S1, NaBH 4 solution (44.55 g / L) and polyethyleneimine solution (2.4 g / L), of which NaBH 4 The injection rate of the solution and the polyethyleneimine solution was 10 mL / min; the mixture was mechanically stirred at a speed of 300 rpm for 30 min until it was uniform and then magnetically separated; the mixture after magnetic separation was washed with anaerobic ethanol and anaerobic water in turn to remove impurities, and then placed in a freeze dryer for 12 h. After drying, it was ground and sieved to obtain biochar loaded with nano zero-valent iron based on dual amino modification, which was named PEI-BC@PEI-nZVI.
[0056] The PEI-modified nZVI loaded with PEI-modified biochar prepared in the above examples was used for material characterization, water V(V) removal experiments, and soil V(V) pollution remediation experiments. The specific conclusions are as follows:
[0057] 1. Characterization (Scanning electron microscope, infrared spectrum analysis, X-ray diffraction analysis):
[0058] Figure 1 The scanning electron microscope image of PEI-BC@PEI-nZVI prepared in Example 1 is shown; Figure 1 As shown, it can be seen that nZVI particles aggregate into nanoclusters and are evenly dispersed on the surface of PBC, indicating the strong dispersion ability of PBC and proving that PEI-BC@PEI-nZVI was successfully prepared.
[0059] Figure 2 The infrared spectrum analysis diagram of PEI-BC@PEI-nZVI prepared in Example 1 is shown; Figure 2 As shown, at 4000cm -1 -500cm -1 In the wave number range, it can be seen that the types of functional groups of PEI-BC@PEI-nZVI have increased significantly compared with nZVI.
[0060] Figure 3 represents the X-ray diffraction analysis diagram of PEI-BC@PEI-nZVI prepared in Example 1, ● represents Fe 0 , ▼ represents Fe 3 O 4 ;like Figure 3 As shown, X-ray diffraction analysis of the material shows that Fe 0 There is a characteristic peak at 2θ = 44.9°, indicating that nZVI was successfully loaded onto PEI-nZVI, PEI-BC@nZVI, and PEI-BC@PEI-nZVI.
[0061] 2. Material selection:
[0062] The adsorption process was as follows: 0.03 ± 0.005 g of PEI-BC@PEI-nZVI with different C / Fe mass ratios was weighed using a balance and added into a 150 mL conical flask. Then, 100 mL of 80 mg / LV(V) solution was added into the conical flask. The initial pH value of the solution was adjusted to 2.0 ± 0.1 with 1 M HCl. After oscillating at 200 rpm for 2 h, the concentration of V(V) in the solution was measured, and the removal rate of the adsorbed material was calculated.
[0063] Figure 4 The diagram shows the adsorption effect of PEI-BC@PEI-nZVI on V(V) under different pH conditions. Figure 5 The graph shows the change trend of PEI-BC@PEI-nZVI adsorption V(V) with time. Figure 6The graph shows the adsorption effect of PEI-BC@PEI-nZVI on V(V) under different temperature conditions. ■ represents 15℃, ● represents 25℃, and ▲ represents 35℃.
[0064] like Figure 4-6 As shown in the figure, the effect of PEI-BC@PEI-nZVI on the removal rate of V(V) was investigated by adjusting the pH value of the solution (2, 4, 6, 8 and 10). The results show that PEI-BC@PEI-nZVI has a good removal effect on V(V) under the condition of pH ≤ 2. The time variation trend of V(V) adsorption by PEI-BC@PEI-nZVI at pH 2.0 and initial concentration of 80 mg / L was studied by adsorption kinetics experiments. Due to the abundant adsorption sites on PEI-BC@PEI-nZVI, the removal rate of V(V) was significantly improved within 30 minutes. Subsequently, with the increase of time, the adsorption sites on PEI-BC@PEI-nZVI gradually decreased, and the removal rate of V(V) showed a slow upward trend and reached equilibrium at 240 minutes. The adsorption of V(V) by PEI-BC@PEI-nZVI at different temperatures (15℃, 25℃, 35℃) was investigated by isothermal adsorption experiments. Under the action of concentration gradient, the removal capacity of PEI-BC@PEI-nZVI for V(V) at various temperatures gradually increases with the increase of concentration, and finally reaches the equilibrium of the reaction, revealing the endothermic characteristics of the adsorption process.
[0065] 3. Soil experiment:
[0066] Experimental conditions: V(V) soil was collected in Sichuan, and impurities were removed. The soil moisture content was adjusted to 40% after passing through a 20-mesh sieve. In this study, three parallel samples were tested simultaneously for each treatment. In soil with a moisture content of 40%, 1% of different types of adsorbents (nZVI, PEI-nZVI, PEI-BC@nZVI, PEI-BC@PEI-nZVI) were applied for a 25-day remediation test. A certain amount of soil samples were taken using the five-point method on the 0th, 3rd, 5th, 17th and 22nd days of remediation, and the V(V) concentration in the soil was determined by the DTPA extraction method.
[0067] Figure 7 represents the content of V (V) in the soil after restoration by different materials in Example 1; Figure 7 As shown in the figure, the content of V(V) in the soil after restoration with different materials. It can be seen that the content of V(V) in the soil of nZVI, PEI-nZVI, PEI-BC@nZVI and PEI-BC@PEI-nZVI gradually decreases, indicating that PEI-BC@PEI-nZVI has the best adsorption effect on V(V) in the soil.
[0068] Figure 8represents the occurrence form of V (V) in the soil after restoration by different materials in Example 1; Figure 8 As shown in the figure, the effect of adding different materials on the change of V occurrence forms in soil was investigated by the Tessier five-step extraction method. V in soil can be divided into exchangeable state, carbonate-bound state, iron-manganese oxide-bound state, organic-bound state and residual state. The addition of different materials can reduce the content of exchangeable and carbonate-bound V in soil, and convert it into iron-manganese oxide-bound state, organic-bound state and residual state. Among them, the soil V morphological transformation in the PEI-BC@PEI-nZVI treatment group was the most significant. It can be seen that PEI-BC@PEI-nZVI treatment helps the transformation of active V in soil to stable V, and reduces the mobility and biological toxicity of V in soil.
[0069] In summary, the PEI-BC@PEI-nZVI prepared in this example is the first highly efficient heavy metal remediation agent for water and soil.
Claims
1. A method for preparing nano zero-valent iron loaded with biochar based on dual amino modification, characterized in that The preparation method is carried out according to the following steps: Step S1: preparing PEI-modified biochar; Under anaerobic conditions, biochar, polyethyleneimine, methanol and pentanediol are mixed with oxygen-free water, placed in a microwave reactor, stirred and reacted for 40 to 80 minutes at a power of 150 to 200 W and a temperature of 60 to 100° C., and then ground and passed through a 100-mesh sieve to obtain PEI-modified biochar; the mass ratio of the biochar to the polyethyleneimine is (5 to 10): (4 to 8); Step S2: preparing PEI-modified biochar loaded with PEI-modified nZVI; In an inert gas environment, FeCl2·4H2O is mixed with oxygen-free water, and then the PEI-modified biochar, NaBH4 solution and polyethyleneimine solution obtained in step S1 are added in sequence, and magnetic separation is performed after mechanical stirring. The mixture after magnetic separation is washed, and then placed in a freeze dryer for drying. After drying, it is ground and sieved to obtain biochar loaded with nano zero-valent iron based on dual amino modification. The mass ratio of the PEI-modified biochar to the polyethyleneimine in the polyethyleneimine solution is (0.49-0.50): (0.12-0.13).
2. The method for preparing nano zero-valent iron loaded with biochar based on dual amino modification according to claim 1, characterized in that The ratio of the mass of biochar, the volume of methanol, the mass of pentanediol and the volume of oxygen-free water described in step S1 is (0.3-0.6) g: (60-120) mL: (0.4-0.8) g: (60-120) mL.
3. A method for preparing nano zero-valent iron loaded with biochar based on dual amino modification according to claim 1 or 2, characterized in that The biochar described in step S1 is prepared according to the following steps: under nitrogen conditions, the soybean straw powder is heated to 300-500°C at a heating rate of 5-10°C / min, and pyrolyzed at 300-500°C for 1-2h. After the pyrolysis is completed, it is crushed through a 100-mesh sieve to obtain biochar.
4. The method for preparing nano zero-valent iron loaded with biochar based on dual amino modification according to claim 1, characterized in that Before mixing FeCl2·4H2O with oxygen-free water in step S2, nitrogen is first passed into the oxygen-free water for 10 to 15 minutes; the ratio of the mass of FeCl2·4H2O to the volume of oxygen-free water is (1.779 to 2.668) g: (120 to 180) mL.
5. The method for preparing nano zero-valent iron loaded with biochar based on dual amino modification according to claim 1, characterized in that The mass ratio of FeCl2·4H2O, PEI-modified biochar and NaBH4 in the NaBH4 solution described in step S2 is (1.779-2.668):(0.49-0.50):(2.22-2.23).
6. A method for preparing nano zero-valent iron loaded with biochar based on dual amino modification according to claim 1 or 5, characterized in that The ratio of the mass of NaBH4 to the volume of distilled water in the NaBH4 solution is (2.22-2.23) g: (40-60) mL; the ratio of the mass of polyethyleneimine to the volume of distilled water in the polyethyleneimine solution is (0.096-0.144) g: (40-60) mL.
7. A method for preparing nano-zero-valent iron loaded with biochar based on dual amino modification according to claim 1 or 5, characterized in that In step S2, the addition interval of PEI-modified biochar, NaBH4 solution and polyethyleneimine solution is 10-15 minutes; the injection speed of NaBH4 solution and polyethyleneimine solution is 8-10 mL / min.
8. The method for preparing nano zero-valent iron loaded with biochar based on dual amino modification according to claim 1, characterized in that In step S2, the rotation speed of the mechanical stirring is 200-300 rpm, and the stirring time is 30-40 min.
9. The method for preparing nano zero-valent iron loaded with biochar based on dual amino modification according to claim 1, characterized in that In step S2, the mixture after magnetic separation is washed with oxygen-free ethanol and oxygen-free water in sequence, and then placed in a freeze dryer for drying for 12 to 14 hours.
10. An application of biochar loaded with nano zero-valent iron based on dual amino modification prepared by the method according to any one of claims 1 to 9, characterized in that The biochar loaded with nano zero-valent iron based on dual amino modification is used to remove vanadium from water and soil.